HAMSTER-healthy, mobility and security-based data communication architecture for unmanned aircraft systems - Pigatto, Daniel Fernando; Goncalves, Leandro [UNESP]; Pinto, Alex Sandro Roschildt [UNESP]; Roberto, Guilherme Freire [UNESP]; Fernando Rodrigues Filho, Julio; Branco, Kalinka Regina Lucas Jaquie Castelo (Institute of Electrical and Electronics Engineers (IEEE), 2014)
Embedded systems are computer systems that are part of a larger system providing generally monitoring and real-time control for the entire system. They provide a set of pre-defined tasks, usually dedicated to a real time application, and have special requirements. These systems are considered critical when failure events may jeopardize lives or high-value assets. Usually these systems operate with frequent information exchange between the inner parts of the vehicle or between the vehicle with ground stations or also with other vehicles. Due to the fact that they are real-time systems, this communication generally requires low latency and security mechanisms that guarantee the basic requirements of a critical scenario, such as confidentiality, integrity, authenticity and availability of communication channels. Furthermore, there is the concern about the vehicles modules/components safety (also known as «health»), which may present malfunctions, whether intentional (attempted attacks) or not, which can lead to vehicle accidents. Given this increasing need to ensure communication and operation of unmanned vehicles plus the desirable characteristic of increasing connectivity in these scenarios, this project proposes the complete specification of a data communication architecture based on safety and mobility concepts. The principal scenario of development will be the aerial, but we expect to obtain a flexible architecture which will be portable to other scenarios of unmanned vehicles, such as ground and water. The specification of the HAMSTER data communication architecture also contributes to the integration of new heterogeneous aircrafts in the airspace, once the requirements for the certification process are being considered. © 2014 IEEE.
Keywords: data communication architecture; HAMSTER; mobility; security; UAS; UAV; unmanned systems